Geokimia Organik Serpih Hidrokarbon Berumur Eosen di Daerah Sumatera Bagian Tengah - Moh. Heri Hermiyanto Zajuli; Riecca Oktavitania; Ollybinar Rizkika (Pusat Survei Geologi, 2020)
This study focused on the region of Central Sumatra that geologically into the Central and South Sumatra Basin. The subjects were from the Eocene shale in the areas such as the Kasiro, Sinamar, and Kelesa Formation. Shale of Central Sumatra Basin tend to have different characteristics with shale of South Sumatra Basin. Maceral content of vitrinite and liptinit on shale in South Sumatra Basin larger than Central Sumatra Basin shale. Oxic-anoxic conditions affecting to the abundance maceral-maceral in both basins. Shale of the Â Kasiro Formation have a tend to indicate kerogen type I, and II, while shale of the Sinamar and Kelesa Formation included into kerogen type I, II and III. Shale from the three formation have the potential as an oil and gas with different characteristics. Shale of the Kasiro Formation shale has the potential source rock which can produce more oil than gas. Meanwhile shale of the Sinamar Formation Â tend to be potentially as the source rock either oil or gas, oil shale and shale gas, but more potential as oil shale. Â Key word : Liptinite, Vitrinite, Eocene, Central Sumatera Basin, South Sumatera Basin